SoTL2: Inquiring into the Impact of Inquiry. (1st June 2016) - Miller‐Young, Janice; Yeo, Michelle; Manarin, Karen; Carey, Miriam; Zimmer, Jim
Abstract : This chapter briefly describes the SoTL research development program and context at Mount Royal University, reports initial results from a study of the program's impact on participants' teaching and scholarly activities, and situates the findings regarding individual impact, department‐level impact, institution‐level impact, and discipline‐level impact within the current literature and the Canadian context.